2001
DOI: 10.1073/pnas.251438898
|View full text |Cite
|
Sign up to set email alerts
|

Import of amber and ochre suppressor tRNAs into mammalian cells: A general approach to site-specific insertion of amino acid analogues into proteins

Abstract: A general approach to site-specific insertion of amino acid analogues into proteins in vivo would be the import into cells of a suppressor tRNA aminoacylated with the analogue of choice. The analogue would be inserted at any site in the protein specified by a stop codon in the mRNA. The only requirement is that the suppressor tRNA must not be a substrate for any of the cellular aminoacyl-tRNA synthetases. Here, we describe conditions for the import of amber and ochre suppressor tRNAs derived from Escherichia c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0
1

Year Published

2002
2002
2011
2011

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(37 citation statements)
references
References 47 publications
1
34
0
1
Order By: Relevance
“…The confirmation of genetically encoded selenoproteins in the plant kingdom presents not only a novel finding, but also raises the possibility for the existence of selenoproteins other than GPX. The finding that a stop codon can be decoded in plants as an amino acid opens new opportunities for engineering plant enzymes to contain nonconventional amino acids, as has been recently described in E. coli (58).…”
Section: Discussionmentioning
confidence: 97%
“…The confirmation of genetically encoded selenoproteins in the plant kingdom presents not only a novel finding, but also raises the possibility for the existence of selenoproteins other than GPX. The finding that a stop codon can be decoded in plants as an amino acid opens new opportunities for engineering plant enzymes to contain nonconventional amino acids, as has been recently described in E. coli (58).…”
Section: Discussionmentioning
confidence: 97%
“…Toward alloprotein synthesis in mammalian cells, nonsense suppression systems have been constructed by the coexpression of a prokaryotic pair of glutaminyltRNA synthetase (GlnRS)⅐tRNA Gln in the cell (26) or by importing the aminoacylated amber suppressor E. coli tRNA Tyr into the cell (45). By using these techniques, the variety of translation systems, together with aaRS engineering, must be further expanded to include mammalian cells.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, the Schultz group has recently engineered an opal suppressor for use in E. coli [66]. Moreover, suppression of both amber and ochre stop codons has been demonstrated in mammalian cells [67]. Attempts have been made to use suppressors of rare codons in E. coli expression systems, and depletion of endogenous tRNAs from the cellfree extract has made this more tractable [68][69][70][71][72].…”
Section: Recoding -Beyond Amber Suppressionmentioning
confidence: 99%
“…This method has the substantial advantage over other in vivo methods that virtually any amino acid can be inserted, but only very small quantities of protein can be produced, requiring very sensitive assays (like voltage clamping). RajBhandary has also shown that acylated tRNA can be introduced into mammalian cells (COS-1 cells) using transfection reagents [67].…”
Section: Microinjection/microelectroporationmentioning
confidence: 99%